Drugs That May Cause or Exacerbate Heart Failure: A Scientific Statement From the American Heart Association. Issue 6 (9th August 2016) - Page, Robert L.; O'Bryant, Cindy L.; Cheng, Davy; Dow, Tristan J.; Ky, Bonnie; Stein, C. Michael; Spencer, Anne P.; Trupp, Robin J.; Lindenfeld, JoAnn
Abstract : Heart failure is a common, costly, and debilitating syndrome that is associated with a highly complex drug regimen, a large number of comorbidities, and a large and often disparate number of healthcare providers. All of these factors conspire to increase the risk of heart failure exacerbation by direct myocardial toxicity, drug-drug interactions, or both. This scientific statement is designed to serve as a comprehensive and accessible source of drugs that may cause or exacerbate heart failure to assist healthcare providers in improving the quality of care for these patients.